2019
DOI: 10.1038/s41598-019-49418-0
|View full text |Cite
|
Sign up to set email alerts
|

Adipose cell size changes are associated with a drastic actin remodeling

Abstract: Adipose tissue plays a major role in regulating whole-body insulin sensitivity and energy metabolism. To accommodate surplus energy, the tissue rapidly expands by increasing adipose cell size (hypertrophy) and cell number (hyperplasia). Previous studies have shown that enlarged, hypertrophic adipocytes are less responsive to insulin, and that adipocyte size could serve as a predictor for the development of type 2 diabetes. In the present study, we demonstrate that changes in adipocyte size correlate with a dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 52 publications
9
42
1
Order By: Relevance
“…Treatment with Rosi partially reversed these morphological changes. Our results are consistent with a recent study that demonstrated correlations between adipocyte size, actin cytoskeletal complexity, and insulin resistance [ 65 ]. These results differ from another study, however, in which it was reported that larger adipocytes with functional declines had reduced actin polymerization [ 66 ].…”
Section: Discussionsupporting
confidence: 93%
“…Treatment with Rosi partially reversed these morphological changes. Our results are consistent with a recent study that demonstrated correlations between adipocyte size, actin cytoskeletal complexity, and insulin resistance [ 65 ]. These results differ from another study, however, in which it was reported that larger adipocytes with functional declines had reduced actin polymerization [ 66 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hasson et al show that in C57BL/6J mice treated with high-fat diet for 2 weeks, Factin increased 4-fold in VAT compared with chow-fat group in response to the intact interaction between IQGAP1 and IRS-1. Reversed feeding correspondingly restored cell size, insulin response, expression of F-actin, and its regulatory proteins [143]. Although this study indicated the critical role of actin in adipocyte remodeling, the effect of cytoskeleton on the structure of adipocytes is quite contrary to the findings in other articles [138,144].…”
Section: Development Of "Supersized" Lipid Dropletcontrasting
confidence: 81%
“…In this study, we have characterized the presence of small surface-associated lipid droplets, rarely recognized before, distinct from the large central droplet which accounts for and determines the cellular volume [30]. Based on microscopy analyses, we propose that these droplet clusters represent an intermediate stage of lipid transport in primary adipocytes.…”
Section: Discussionmentioning
confidence: 80%